(untitled) (Research, Society and Development, 2020)
Wax deposition is an old problem in the oil industry. Due to the economic losses, several studies have been conducted in order to understand it. In the literature, deposition mechanisms are commonly used in models for the prediction of this phenomenon, with emphasis on the mechanisms of molecular diffusion and shear dispersion and removal. Given the importance of deposition mechanisms in the representation of paraffin deposition, this paper aims to carry out a brief review of the main mechanisms addressed in the literature and their use in depositional models. The review carried out showed that paraffin deposition is not completely understood, and that the adoption of mechanisms to represent it must be linked to the boundary conditions of the problem. In addition, it was possible to notice that few models available in the literature deal with mechanisms other than molecular diffusion or shear dispersion and removal.